Clinical and Antimicrobial Evaluation of Copaifera langsdorffii Desf. Dental Varnish in Children: A Clinical Study. (26th March 2021) - Valadas, Lídia Audrey Rocha; Lobo, Patrícia Leal Dantas; Fonseca, Said Gonçalves da Cruz; Fechine, Francisco Vagnaldo; Rodrigues Neto, Edilson Martins; Fonteles, Marta Maria de França; Aguiar Trévia, Lorena Ribeiro de; Vasconcelos, Hilda Lara Prado; Lima, Sandra Mara da Silva; Lotif, Mara Assef Leitao; Fernandes, Analice Mendes Barreto; Bandeira, Mary Anne Medeiros
Abstract : Background . The objective of this study was to evaluate the clinical and microbiological efficacies of ( C. langsdorffii ) dental varnish in children at high risk of dental caries.. Methods . This is a longitudinal, randomized, controlled clinical trial. Ninety high-risk caries-free children (ICDAS II = 0) were recruited and randomly divided into three groups: C. langsdorffii, chlorhexidine, or fluoride. The varnishes were applied on the second deciduous molars for three times: baseline (D0), after 90 days (D90), and after 180 days (D180). Saliva was collected on D0, D90, D180, and D360 to evaluate S. mutans reduction. Statistics were carried out by ANOVA, Tukey's test, and the paired t -test. Results . Copaiba varnish demonstrated significant S. mutans reduction: D360 versus D0 p < 0.0001, D180 versus D0 p < 0.001, D360 versus D90 p < 0.001, D180 versus D90 p < 0.001, and D360 versus D180 p < 0.05 . Chlorhexidine varnish significantly reduced S. mutans at D180 versus D0 p < 0.05 . Fluoride reduced at D180 versus D0 p < 0.001 . Conclusions . Three annual applications of this varnish showed substantial antimicrobial activity against S. mutans and caries prevention for up to 12 months.